Activated carbon production from horse chestnut shells for hydrogen storage - Işınkaralar, Kaan; Güllü, Gülen; Türkyılmaz, Aydın; Doğan, Mehmet; Turhan, Onur (Inderscience Publishers, 2022)
Doğan, Mehmet (Balikesir Author) ; New generation clean energy resources can be defined as hydrogen energy. However, the search for techniques accelerated in hydrogen energy converting and storing. In the study, the hydrogen storage capacity of activated carbon was obtained from horse chestnut shells, which is a lignocellulosic waste. It was investigated at cryogenic temperature and room temperature. The raw material's surface area and micropore volume have been increased by chemical activation methods using an activation agent (ZnCl2). Physicochemical analysis of activated carbon was also carried out. As a result of the research, the highest efficiency under constant pressure was obtained as 3.18 wt%.
Keywords: Activated Carbon; Physicochemical; Hydrogen Storage; Horse Chestnut Shell; HCS